2000
DOI: 10.1007/s004200050024
|View full text |Cite
|
Sign up to set email alerts
|

Risk of lung cancer in workers producing stainless steel and metallic alloys

Abstract: This study failed to detect any relationship between lung cancer and exposure to iron, chromium, nickel and/or their compounds. High and statistically significant relative risks, along with increasing trends, were observed for simultaneous exposure to PAHs and silica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 23 publications
4
35
0
Order By: Relevance
“…The observed low mortality is very similar to that reported in other industries in France (Moulin et al 2000). Although this study is on the whole quite powerful, it lacked statistical power and precision to assess specific causes of death, particularly in view of the average age (48 years old).…”
Section: Discussionsupporting
confidence: 81%
“…The observed low mortality is very similar to that reported in other industries in France (Moulin et al 2000). Although this study is on the whole quite powerful, it lacked statistical power and precision to assess specific causes of death, particularly in view of the average age (48 years old).…”
Section: Discussionsupporting
confidence: 81%
“…A nonsignificantly increased risk of oral and pharyngeal cancer was found in the two studies of coke workers (Hurley et al 1983;Swaen et al 1991), but studies of foundry workers (Hoshuyama et al 2006;Moulin et al 2000b;Sherson et al 1991;Sorahan et al 1994) did not show results consistent enough for a definitive conclusion. Evanoff et al (1993) studied a cohort of chimney sweeps and found an increased incidence of cancer of OC and pharynx.…”
Section: Cohort Studiesmentioning
confidence: 84%
“…Although numerous studies suggest that there is an association between exposure to iron fumes or dust at work and lung cancer risk (11)(12)(13)(14), the possible effect from other agents in simultaneous exposure could not be ruled out completely. Exposure to iron fumes or dust and welding fumes is associated because the main constituent of welding fumes is iron and its compounds.…”
mentioning
confidence: 99%